Evaluation of agricultural and food wastes as alternative substrate components for cultivation of white oyster mushroom Pleurotus floridanus singer / Umahsreerekah Gopala Krishnan - Umahsreerekah , Gopala Krishnan (2019)
The demand for oyster mushrooms in Malaysia is increasing due to the health benefits. However, there are some challenges and obstacles faced by the mushroom industry including lack of supply and increasing price of raw materials which greatly burden the mushroom growers. Thus, mushroom growers are seeking alternative lignocellulosic substrates to reduce the cost of production. The objectives of this study were to optimise the substrate formulation, to evaluate the growth performance and production yield as well as to analyse the nutrient profile of Pleurotus floridanus (strains PF1 and PF2) basidiocarps grown in the standard substrate supplemented with coffee waste (CW), food waste compost (FWC) and empty fruit bunch compost (EFBC) of varying concentrations (10%, 20%, 30% and 40% w/w). In order to select the suitable concentration of these three supplements, linear growth study were conducted. Strain PF1 displayed variable growth rate and mycelium density on each of the waste formulations. The selected CW, FWC and EFBC used for cultivation of PF1 strain were10% (w/w) at 0.37 ± 0.02 cm/day, 10% (w/w) (0.52 ± 0.02 cm/day) and 20% (w/w) (0.61 ± 0.02 cm/day) respectively. Meanwhile for PF2 strain, the most suitable concentrations of standard substrate supplemented with CW, FWC and EFBC were 10% (0.38 ± 0.02 cm/day), 20% (0.52 ± 0.02 cm/day) and 30% (0.65 ± 0.02 cm/day), respectively. In yield of fruiting bodies, the highest yield per bag obtained was PF1 strain grown in standard substrate supplemented with 10% (w/w) FWC (83.37 ± 24.25g), while the lowest production recorded in PF1 strain grown in substrate supplemented with standard substrate (79.26 ± 14.16).PF2 strain produced the highest of77.62 ± 34.23g yield per bag in standard substrate and the lowest yield of 52.93 ± 25.53g in standard substrate supplemented with 30% (w/w) EFBC. In terms of number of harvests per cycle, PF1 fruiting bodies were able to harvest until 4th harvests. Fruiting bodies of PF1 strain were selected for nutrient profiling compared to fruiting bodies of PF2 strain, as it had the fastest spawn run time, produced more harvest cycles, obtained higher yield and BE as well as zero contamination rate in bags. Total sugar content and beta glucan content (75.12 ± 0.03 mg/g and 33.19%, respectively) were found the highest in the fruiting bodies grown on standard substrate while total phenolic content at 21.99 ± 0.01 mg/g and total protein content (200 ± 0.01 mg/g) were found the highest in standard substrate supplemented with CW and FWC, respectively. The findings from this study showed that these wastes can be considered as supplements in standard substrates for P. floridanus cultivation.